Innovation in Installing Tolerance Values in the Prophet's Sirah Through Comic Media as a Creative Educational Media in Dealing with Intolerant Attitudes - Aini, Fadhilah; Husna, Nurul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The civilization of a nation can be measured by the moral and moral quality of its people. Improving moral quality can be taken through the learning process both in formal, non-formal and informal environments.  A good understanding of tolerance is one of the things discussed in moral education to answer the plurality of society in Indonesia. Comic media is a creative media that can increase students' understanding and motivation about the meaning of tolerance in social life. This study aims to design media innovations based on tolerance values through the historical approach of the Nabawiyah sirah by making media schemes, how media work and the potential success of the media. This research uses Research and Development (RD) type ADDIE (Analysis, Design, Development, Implementation, Evaluation) type of research. The series of media is made as interesting as possible, namely making comic media accompanied by contemporary problems and presenting the story of the history of Nabawiyah to provide a better understanding of the meaning of tolerance. The history of the Medina charter became a story included in the comics to serve as an example of tolerance. The use of games as an evaluation of students' understanding of the material conveyed in comics. The main contribution of this research is to create an innovative media to instill the value of tolerance through the Nabawiyah sirah which can be used as a reference for educators and further media development.